DIGITAL LITERACY AND ERP TECHNOLOGY ADOPTION IN BOSNIA AND HERZEGOVINA - Ensar Mekić; Adis Maksić; Belmin Hadžimusić (Economic Review)
Even though the Enterprise Resource Planning (ERP) technologies have been significantly addressed in managerial literature, few studies investigated the effects of digital literacy. This study aims to explore the relationship between digital literacy and ERP technology adoption in Bosnia and Herzegovina (BiH), as well as the mediating effects of business innovativeness within that relationship. A valid and reliable structured survey has been prepared and delivered to companies in BiH which use ERP technologies. Based on the recent literature, first order structural equation model has been proposed and tested. The empirical data was based on 82 questionnaire responses from companies in BiH which use ERP technologies. Once the data has been collected, factory data analysis has been performed to purify scales through items' loadings and Cronbach's Alpha values. The resultant scales have been tested for convergent validity through partial least-square path modelling using Smart PLS 3 software. The results indicated that effects of digital literacy on actual system use are significant and positive, and that business innovativeness partially mediates the relationship.